2018
DOI: 10.4108/eai.13-7-2018.155082
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Autism in Urban Bangladesh: Unpacking Infrastructural and Cultural Challenges

Abstract: Autism Spectrum Disorder (ASD) is a critical problem worldwide; however, low and middle-income countries (LMICs) often suffer more from it due to the lack of contextual research and effective care infrastructure. Moreover, ASD in LMICs offers unique challenges as cultural misperceptions and social practices often impede effective care there. However, the recent growth in mobile phone adoption in many LMICs has created a timely opportunity for improving ASD care practices through digital means. We present quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, the findings of this study suggest that increasing awareness of ASD by using varying means, including ICT, could help to overcome the stigma against people with ASD that has been associated with social and cultural issues [48]. This is supported by Ehsan et al [49], who found a lack of contextualized studies on ASD in less developed countries while the number of people with ASD continues to increase.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, the findings of this study suggest that increasing awareness of ASD by using varying means, including ICT, could help to overcome the stigma against people with ASD that has been associated with social and cultural issues [48]. This is supported by Ehsan et al [49], who found a lack of contextualized studies on ASD in less developed countries while the number of people with ASD continues to increase.…”
Section: Discussionmentioning
confidence: 63%
“…As a developing country, Rwanda has a lack of digital infrastructure that is a challenge and can lead to reduced support for people with ASD [49]. This supports studies which prove that digital technologies, when used effectively, can deliver foundational educational content to any learner so they can respond to the needs of people with ASD from different geographical contexts [40,50].…”
Section: Discussionmentioning
confidence: 75%
“…These are samples of areas where accessible, affordable, and scalable precision medicine solutions, such as instantiations of the technique described here, can enable access to care to underserved populations globally. In particular, we selected Bangladesh, Kenya, and the Philippines, countries that collectively represent diverse areas containing problematic issues with autism prevalence and limited access to services [ 46 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Caring for children with ASD is challenging and impacts family life [ 28 , 29 ]. The satisfaction of needs of affected children requires a lot of time, patience, and exertion, and can cause depression, anxiety, and psychological distress among their parents and caregivers [ 30 – 33 ].…”
Section: Introductionmentioning
confidence: 99%